A Brief History of Everyone Who Ever Lived : The Stories in Our Genes - Adam Rutherford (Weidenfeld & Nicolson, 2016)
This is a story about you. It is the history of who you are and how you came to be. It is unique to you, as it is to each of the 100 billion modern humans who have ever drawn breath. But it is also our collective story, because in every one of our genomes we each carry the history of our species - births, deaths, disease, war, famine, migration and a lot of sex. Since scientists first read the human genome in 2001 it has been subject to all sorts of claims, counterclaims and myths. In fact, as Adam Rutherford explains, our genomes should be read not as instruction manuals, but as epic poems. DNA determines far less than we have been led to believe about us as individuals, but vastly more about us as a species. In this captivating journey through the expanding landscape of genetics, Adam Rutherford reveals what our genes now tell us about history, and what history tells us about our genes. From Neanderthals to murder, from redheads to race, dead kings to plague, evolution to epigenetics, this is a demystifying and illuminating new portrait of who we are and how we came to be.